Particularities of Golija nature park and conditions for further development of rural tourism - Mijajlović, Nada; Vuković, Predrag; Djurić, Ivan (Economics of Agriculture, 2010)
Nature Park "Golija"is a mountainous area in Serbia with big the ecological and tourist potentials. The paper discusses the possibilities for development of rural tourism in the context of sustainable development and multifunctional agriculture, on the basis of present resources. Predisposition for the development of tourism is based next to the natural attractions and to develop local brands, which would be based on the improvement of livestock, dairy and meat production of autochthonous products for which there is a fair demand in the market. The standardization of the technological process of obtaining Golija cheese as a unique autochthonous dairy product is an activity that contributes to achieving the objective of improving the tourist offer Golija region.